Enhanced Stability and Emission Properties of Perylene Dyes by Surface Tethering: Preparation of Fluorescent Ru Nanoparticle Suspensions by Alkyne Linker Chemistry. Issue 3 (3rd December 2020) - Morais, Eduardo; Moloney, Cara; O'Modhrain, Colin; McKiernan, Eoin; Brougham, Dermot F.; Sullivan, James A.
Abstract: Spherical ruthenium nanoparticles (NPs) with a narrow size distribution were synthesised in ethanol by a facile low‐temperature solvothermal process without the assistance of templates, structure‐directing agents or post annealing/reduction treatments. Surface passivation with a fluorescent perylene dye (EP), and with silane ligands (ETMS), both initially bearing alkyne groups and subsequently forming vinylidene linkages, provided stable suspensions of the marginally soluble free EP. Quantitative analysis of the suspension gave an estimated EP surface coverage of 15 %, corresponding to an EP/ETMS mole ratio of ≈1:6. Photophysical evaluation of the bound and free dye revealed similar absorption bands and extinction coefficients and improved properties for the bound state, including enhanced fluorescence in the visible range for the bound dye, an extended absorption range into the near‐UV providing strong emission in the visible, and significantly improved photostability. The physical basis of the enhanced photophysical properties, potential routes to further improvements and the implications for applications are discussed. Abstract : Support groups : Ru 0 nanoparticles were prepared, and their surfaces were modified through the formation of vinylidene linkages with a perylene dye and a Si‐containing alkyne. The vinylidene groups stabilize the Ru 0 nanoparticles against precipitation, and the Ru 0 nanoparticles enhance the absorption and emission properties (and the stability) of the alkyne‐containing perylene dyes.